2018
DOI: 10.1155/2018/6847971
|View full text |Cite
|
Sign up to set email alerts
|

Niosome: A Promising Nanocarrier for Natural Drug Delivery through Blood-Brain Barrier

Abstract: Niosomes (the nonionic surfactant vesicles), considered as novel drug delivery systems, can improve the solubility and stability of natural pharmaceutical molecules. They are established to provide targeting and controlled release of natural pharmaceutical compounds. Many factors can influence on niosome construction such as the preparation method, type and amount of surfactant, drug entrapment, temperature of lipids hydration, and the packing factor. The present review discusses about the most important featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
141
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(143 citation statements)
references
References 76 publications
1
141
0
1
Order By: Relevance
“…Niosomes have the ability to entrap lipophilic or hydrophilic drugs and are able to deliver the drug molecules at target site in a sustained and/or controlled manner [56,57]. Niosomes have been reported to modify drugs organ distribution and metabolic stability [58]. It has been shown that surface modification of the niosomes promotes the target specificity for the cancer drug delivery system.…”
Section: Niosomesmentioning
confidence: 99%
“…Niosomes have the ability to entrap lipophilic or hydrophilic drugs and are able to deliver the drug molecules at target site in a sustained and/or controlled manner [56,57]. Niosomes have been reported to modify drugs organ distribution and metabolic stability [58]. It has been shown that surface modification of the niosomes promotes the target specificity for the cancer drug delivery system.…”
Section: Niosomesmentioning
confidence: 99%
“…The specific color of MB is due to the strong absorption band in the 550-700 nm regions with maximum molar absorptivity of 85,000 M−1 cm−1 at 664nm [11]. Methylene blue is a molecule having vital roles in microbiology and pharmacology; moreover it is used to stain living organisms considered as a Photosensitizer for photodynamic therapy [12][13][14][15][16]. Niosomes (the nonionic surfactant vesicles) can improve the solubility as well as the stability of pharmaceutical molecules since niosomes can act as drug reservoirs, can be a carrier for hydrophilic and hydrophobic drugs and has the adjusting effect on drug release rate [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, topical application of niosomes has an increasing effect on the residence time of drugs in the stratum corneum and epidermis. Moreover, non-ionic surfactants normally show favorable dermatological properties [16]. Skin is a vital organ offering an appropriate site for administration of many drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Niosomes are novel drug delivery system, in which the medicament is encapsulated in a vesicle. The vesicle is composed of a bilayer of non ionic surfactant and cholesterol (Gharbavi et al, 2018). A bioadhesive material (polymer) coated niosomal formulation of anti-infective agent was purposed to show a longer retention time on eye and subsequent reduction in dosing frequency.…”
Section: Introductionmentioning
confidence: 99%